Appraisal of the orofacial rehabilitation effects and their influence on social acceptance of children with Down’s Syndrome - Szklarska, Ewa (2008)
In children with the DS numerous anatomical and functional abnormalities of masticatory system occur, which require orthodontic intervention. The aim of ortodontic therapy is to increase of the face muscular tension, the improvement of the face appearance and correction of the disturbed function. The study material consisted of 139 individuals, aged from 1 month to 13 years. Rehabilitation lasted on an average thirty month and was conducted by parents under supervision of the orthodontist. The scope of orofacial rehabilitation methods applied in children with DS included: massage of the oral cavity and the face, stimulating plate according to Castillo-Morales, other appliances. The anthropometric measurements of heads of children with DS were compared with those of healthy children of the same age and in majority of inspected features the clear, statistically essential differences were observed. The dimensions of heads in children with DS were smaller than in healthy children. After the rehabilitation in majority of inspected features we didn’t observe any differences. The outcomes of clinical examination of masticatory organs taken before and after the rehabilitation in children with DS were compared and the effectiveness of the rehabilitation was assessed. An improvement of facial appearance and dentition were observed and also an improvement of examined functions of masticat
Keywords: social acceptance; antropometric measurment; orofacial rehabilitation; Down’s Syndrome